Silkwood [videorecording (DVD)] - Streep, Meryl; Russell, Kurt; Cher, 1946-; Nelson, Craig T. (KL studio classics., 2017)
The story of Karen Silkwood, the Oklahoma nuclear facility worker who blew the whistle on dangerous practices at the Kerr-McGee plant and who died under circumstances which are still under debate.